Interactive Teaching in Writing Session of English Department Students - Wirhayati Wirhayati (Lexeme : Journal of Linguistics and Applied Linguistics, 2020)
Interactive writing is a writing process used to teach students how to write a paragraph. The process involves the sharing of writing between the teacher and students. It can be in a group of students. The purpose of this research was to know the development of writing skill in the students of English Department through interactive method. All participants were the students of the English Department Faculty of Letters of Pamulang University. Interactive writing is an effective method as the teacher role is very important. A Theory used is Brown’s theory (2000). The procedure is to teach students how to write well by allowing them to directly copy the demonstration of the teacher. Interactive writing helps students improve their writing skills as using the same example as the teacher and creates the right mindset for the students to copy the technique of writing a paragraph by the teacher correctly. By directly following the guide of the teacher, the students writing is better than they use their own writing.  As an introduction to writing, interactive writing is a useful and successful technique for teachers to use in teaching the basics.